Nimodipine-Induced Blood Pressure Changes Can Predict Delayed Cerebral Ischemia - Fischer, Corinne; Goldberg, Johannes; Vulcu, Sonja; Wagner, Franca; Schöni, Daniel; Söll, Nicole; Hänggi, Matthias; Schefold, Jörg; Fung, Christian; Beck, Jürgen; Raabe, Andreas; Z'Graggen, Werner J. (Frontiers in Neurology, 2019)
Background: Early diagnosis of delayed cerebral ischemia (DCI) in patients after aneurysmal subarachnoid hemorrhage (aSAH) still poses a leading problem in neurointensive care. The aim of this study was to analyze the effect of oral Nimodipine administration on systemic blood pressure in patients with evolving DCI compared to patients without DCI. Methods: Systolic (SBP), mean (MAP) and diastolic (DBP) blood pressures were analyzed at the time of Nimodipine administration and additionally 30, 60 and 120 minutes thereafter on days 1, 3 and 5 after aSAH. Additionally, the 24 hours period preceding DCI and in patients without DCI day 10 after aSAH were analyzed. Statistical analysis was performed for SBP, MAP and DBP at time of Nimodipine administration and for the maximal drop in blood pressure after Nimodipine administration. Results: 30 patients with aSAH were retrospectively analyzed with 17 patients developing DCI (“DCI”) and 13 patients who did not (“Non-DCI”). DCI patients showed a more pronounced rise in MAP and DBP over the examined time period as well as a higher decrease in SBP following Nimodipine administration. A fall of 18 mmHg in SBP after Nimodipine administration showed a sensitivity of 82.4% and specificity of 92.3% for occurrence of DCI. Conclusion: An increase of MAP and DBP after aSAH and a heightened sensitivity to Nimodipine administrations may serve as additional biomarkers for early detection of evolving DCI.